Other-Regarding Preferences and Incentives in the Societal Context - Jenny Kragl; Benjamin Bental (ZBW - Leibniz Information Centre for Economics, 2020)
The article is concerned with understanding the impact of social preferences and wealth inequality on aggregate economic outcomes. We investigate how different manifestations of other-regarding preferences affect incentive contracts at the microeconomic level and how these in turn translate into macroeconomic outcomes. Increasing the workers' sensitivity to inequality raises effort and reduces wage costs for poor but not necessarily for rich workers. A parameterized version of the model roughly mimicking relevant key features of the industrialized world shows that, at the general equilibrium, increased initial wealth differences raise aggregate profit and output but entail distributional utility losses and increased inequality.
Keywords: D31; D50; D63; D82; M52; M54; 330; other-regarding preferences; incentives; general equilibrium; inequality; wealth; income; inequality aversion; competitiveness